Cancer Risk Assessment of Trihalomethanes Exposure in Tap and Swimming Pool Water in Kuantan Hotel - Marekan, M. E. S.; Afiza, Abdullah Suhaimi; N. M., Hussin; R. A., Romzay (Penerbit Universiti Malaysia Pahang, 2016)
Chlorination is a common disinfection method for tap and swimming pool water as it is the most effective and low-cost method compared with others. The purpose of the study was to assess cancer risk of THMs exposure in tap and swimming pool water in Kuantan hotels. Temperature and pH were analyzed as an in-situ measurement while the rest of the parameters were analyzed in the laboratory. The concentration of four forms of THMs in tap and swimming pool water analyzed from Hotel X are 1.23ug/L and 1.35ug/L for CHCl3 respectively and none for the CHCl2Br, CHClBr2 and CHBr3. The concentration of four forms of THMs in tap and swimming pool water at Hotel Y are 1.25ug/L and 1.18ug/L respectively for CHCl3 and none for the CHCl2Br, CHClBr2 and CHBr3. The cancer risk from exposure to THMs at Hotel X are 1.6 x 10-5 for tap water, 1.9 x 10-5 for swimming pool water and 2.0 x 10-4 for both tap and swimming pool water while cancer risk from exposure to THMs at Hotel Y are 1.7 x 10-5 for tap water, 1.6 x 10-5 for swimming pool water and 1.19 x 10-4 for both tap and swimming pool water.Thus, it shows that, it is in range of acceptable risk.